Highly Selective CO2 Electroreduction to CH4 by In Situ Generated Cu2O Single‐Type Sites on a Conductive MOF: Stabilizing Key Intermediates with Hydrogen Bonding. (26th October 2020) - Yi, Jun‐Dong; Xie, Ruikuan; Xie, Zai‐Lai; Chai, Guo‐Liang; Liu, Tian‐Fu; Chen, Rui‐Ping; Huang, Yuan‐Biao; Cao, Rong
Abstract: It is still a great challenge to achieve high selectivity of CH4 in CO2 electroreduction reactions (CO2 RR) because of the similar reduction potentials of possible products and the sluggish kinetics for CO2 activation. Stabilizing key reaction intermediates by single type of active sites supported on porous conductive material is crucial to achieve high selectivity for single product such as CH4 . Here, Cu2 O(111) quantum dots with an average size of 3.5 nm are in situ synthesized on a porous conductive copper‐based metal–organic framework (CuHHTP), exhibiting high selectivity of 73 % towards CH4 with partial current density of 10.8 mA cm −2 at −1.4 V vs. RHE (reversible hydrogen electrode) in CO2 RR. Operando infrared spectroscopy and DFT calculations reveal that the key intermediates (such as *CH2 O and *OCH3 ) involved in the pathway of CH4 formation are stabilized by the single active Cu2 O(111) and hydrogen bonding, thus generating CH4 instead of CO. Abstract : Cu2 O(111) single‐type sites on a conductive metal–organic framework are successfully prepared by an in situ electrochemical method. The cooperative effect between the single active Cu2 O(111) and hydrogen bonding contributes to the high selectivity of 73 % towards CH4 with large current density in CO2 electroreduction reduction for the obtained Cu2 O(111)@CuHHTP.